The Gold Investment Strategy Education as a Low-Risk Investment Opportunit : Edukasi Strategi Investasi Emas sebagai Peluang Investasi Minim Risiko - Indriani, Agustina; Saminem; Hasibuan, Ahmad Basid Hasibuan; Modjaningrat, Radina; Isniawati, Atik; Jombrik TPR (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
The educational seminar "Gold Investment Strategy as a Low-Risk Investment Opportunity" was held to contribute to improving financial literacy for students and the general public amidst the uncertain economic situation. This seminar aimed to provide a fundamental understanding of gold investment, both physical and digital, as a hedge against inflation. Through an educational-participatory approach, participants gained not only theoretical knowledge but also hands-on practice using official and secure investment platforms such as Pegadaian Digital, BSI Mobile, and logammulia.com. The seminar was held offline in Room 209, Faculty of Economics, Darma Persada University, in July 2025, and was attended by 48 participants. Evaluation results indicated an increase in participants' understanding, interest, and readiness to manage their personal finances through wise and planned gold investment.